A three-year, multi-parametric MRI study in patients at presentation with CIS - Rocca, M. A.; Agosta, F.; Sormani, M. P.; Fernando, K.; Tintorè, M.; Korteweg, T.; Tortorella, P.; Miller, D. H.; Thompson, A.; Rovira, A.; Montalban, X.; Polman, C.; et al. (Journal of neurology, 2008)
Objectives To define the extent of overall brain damage in patients with clinically isolated syndromes (CIS) suggestive of multiple sclerosis (MS) and to identify non-conventional magnetic resonance (MR) metrics predictive of evolution to definite MS. Methods Brain conventional and magnetization transfer (MT) MRI scans were obtained from 208 CIS patients and 55 matched healthy controls, recruited in four centres. Patients were assessed clinically at the time of MRI acquisition and after a median period of 3.1 years from disease onset. The following measures were derived: T2, T1 and gadolinium (Gd)- enhancing lesion volumes (LV), normalized brain volume (NBV), MTR histogram-derived quantities of the normal-appearing white matter (NAWM) and grey matter (GM). Results During the follow-up, 43 % of the patients converted to definite MS. At baseline, a significant inter-centre heterogeneity was detected for T2 LV (p = 0.003), T1 LV (p = 0.006), NBV (p < 0.001) and MTR histogram-derived metrics (p < 0.001). Pooled average MTR values differed between CIS patients and controls for NAWM (p = 0.003) and GM (p = 0.01). Gdactivity and positivity of International Panel (IP) criteria for disease dissemination in space (DIS), but not NAWM and GM MTR and NBV, were associated with evolution to definite MS. The final multivariable model retained only MRI IP criteria for DIS (p = 0.05; HR = 1.66, 95 % CI = 1.00–2.77) as an independent predictor of evolution to definite MS. Conclusions Although irreversible tissue injury is present from the earliest clinical stages of MS, macroscopic focal lesions but not "diffuse" brain damage measured by MTR are associated to an increased risk of subsequent development of definite MS in CIS patients.